West Indian Med J 2016
DOI: 10.7727/wimj.2015.327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Dyslipedemia in Obese and Diabetic Patients of Rural and Urban Areas in Lahore, Pakistan

Abstract: Objective: Obesity and diabetes mellitus are interconnected conditions that share a number of pathophysiological mechanisms such as dyslipidemia leading to cardiovascular complications. The present study was conducted to determine the individual and combined effect of diabetes mellitus and obesity on dyslipidemia and ultimately on silent coronary artery disease (CAD). Methods:The patients selected from urban and rural areas of Lahore were recruited on the basis of body mass index (BMI) and fasting blood sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Further, it has been proven that dyslipidemia was associated with blood glucose [ 26 , 30 ]. Our results showed that TG level was positively correlated with FBG, and displayed an increasing trend for both males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been proven that dyslipidemia was associated with blood glucose [ 26 , 30 ]. Our results showed that TG level was positively correlated with FBG, and displayed an increasing trend for both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study in China found that DM was more common in urban areas [ 6 ], and we found that living in urban places could increase level of FBG (except in the high quantiles of FBG). This may be associated with a sedentary lifestyle and dietary changes [ 30 , 35 ]. Plenty of epidemiological and randomized clinical studies have suggested that lifestyle interventions would have beneficial effects on FBG [ 36 , 37 ], such as diet control, weight control, and alcohol control, etc.…”
Section: Discussionmentioning
confidence: 99%